Efecto del extracto etanólico de Annona muricata a diferentes tiempos y concentraciones sobre el ciclo celular en Allium cepa - Chávez Aldave, Maruja Isabel (2015)
The objective of this study was to determine the effects of an ethanolic extract of Annona muricata, or Guanábana, applied for various exposure periods in concentrations of 25 µg/mL, 50 µg/mL and 100 µg/mL on the cell cycle of root meristems of the Roja Arequipeña variety of onion, Allium cepa. The twelve treatments of ethanolic extract of Annona muricata used to induce growth in the onion roots were as follows: T1: 0 µg/mL for 6 hours, T2: 25 µg/mL for 6 hours, T3: 50 µg/mL for 6 hours, T4: 100 µg/mL for 6 hours, T5: 0 µg/mL for 12 hours, T6: 25 µg/mL for 12 hours, T7: 50 µg/mL for 12 hours, T8: 100 µg/mL for 12 hours, T9:0 µg/mL for 24 hours, T10: 25 µg/mL for 24 hours, T11: 50 µg/mL for 24 hours and finally T12: 100 µg/mL for 24 hours. After exposing the roots to the treatment, the cells were mounted on slides, stained, and examined microscopically. Results of microscope analysis demonstrates that treatment T12, an ethanolic extract of Annona muricata at a concentration of 100 µg/mL over a 24 hour exposure period, reduces the Mitotic index by up to 7.52%, with a 87.93% increase in the Prophasic index, and 5.98, 4.43, and 1.33% reductions in the Metaphasic, Anaphasic, and Telophasic indices respectively, strongly implying the presence of oxidizing compounds in the Annona muricata ethanolic extract, which may indicate potential as a future alternative to antineoplastic therapy.